A 3D upper bound limit analysis using radial point interpolation meshless method and second‐order cone programming. (5th May 2016) - Yu, Shengbing; Zhang, Xue; Sloan, S. W.
Summary: This paper presents a 3D formulation for quasi‐kinematic limit analysis, which is based on a radial point interpolation meshless method and numerical optimization. The velocity field is interpolated using radial point interpolation shape functions, and the resulting optimization problem is cast as a standard second‐order cone programming problem. Because the essential boundary conditions can be only guaranteed at the position of the nodes when using radial point interpolation, the results obtained with the proposed approach are not rigorous upper bound solutions. This paper aims to improve the computing efficiency of 3D upper bound limit analysis and large problems, with tens of thousands of nodes, can be solved efficiently. Five numerical examples are given to confirm the effectiveness of the proposed approach with the von Mises yield criterion: an internally pressurized cylinder; a cantilever beam; a double‐notched tensile specimen; and strip, square and rectangular footings. Copyright © 2016 John Wiley & Sons, Ltd.